Web-based education concepts, methodologies, tools and applications - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
"This comprehensive collection offers a compendium of research on the design, implementation, and evaluation of online learning technologies, addressing the challenges and opportunities associated with the creation and management of Web-based applications and communities, instructional design, personalized learning environments, and effective educational delivery"--Provided by publisher.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on Aug. 23, 2010).
Keywords: Web-based instruction; Computer-assisted instruction; Web-based instructional design; Virtual learning environments; Online learning communities; Learning management systems; Educational technology; E-learning using Wikis and blogs; Dynamic learning environments; Online assessment; Asynchronous and synchronous e-learning; Electronic books